2013
DOI: 10.1088/1674-1056/22/8/083303
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies on the shape effect of Fe84.94Si9.68Al5.38particles on their microwave permeability

Abstract: Ball milling for long time (such as 10, 20, and 30 h) can transform Fe 84.94 Si 9.68 Al 5.38 alloy powders with irregular shapes into flakes. X-ray diffraction (XRD) and Mössbauer measurements have proven that the unmilled particles and the flakes obtained by milling for 10 h have the same D0 3 -type superlattice structure. The flakes obtained by milling for 20 h and 30 h have the same disorder α-Fe(Si, Al) structure. There are more than 6 absorption peaks in the transmission Mössbauer spectra (TMSs) for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[5][6][7][8] However, these methods can result in poor compositional control, size inhomogeneity, and phase impurity. Han and Deng, [9] Yu et al, [10] Ren and Zhang, [11] and Tian et al [12] also have reported that the magnetic properties of the magnetic materials considerably depended on their shapes, structures, and doped metals. In order to obtain the ferrite with good properties, an appropriate preparation method must be used.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] However, these methods can result in poor compositional control, size inhomogeneity, and phase impurity. Han and Deng, [9] Yu et al, [10] Ren and Zhang, [11] and Tian et al [12] also have reported that the magnetic properties of the magnetic materials considerably depended on their shapes, structures, and doped metals. In order to obtain the ferrite with good properties, an appropriate preparation method must be used.…”
Section: Introductionmentioning
confidence: 99%